Controlled Legal Pluralism: Islamic Family Law Adaptation In Socialist-Secular China - Agus Irfan; M Saeful Amri; Warsiyah Warsiyah; M Ali Munkhakim; Dian Naeli Sa'adah (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
Islamic family law is the legal domain most directly confronted by state legal dominance in modern legal systems, particularly when the state places all family relations under a single formal legal framework. In China, the socialist-secular legal order affirms that marriage, divorce, inheritance, and domestic relations are governed exclusively by the Civil Code of the People’s Republic of China, thereby excluding religious norms from formal recognition as a legal source. Existing studies on Islam and the state in China have largely focused on Muslim minority identity and religious regulation. Yet, they have not sufficiently explained how Islamic family law survives under conditions of legal centralization and strict administrative control. This study aims to analyze the forms of adaptation of Islamic family law within Muslim minority communities in China using a qualitative socio-legal approach, employing normative analysis of national legal regulations, administrative policies, and recent academic literature. The findings show that Islamic family law does not function as a formal legal system but survives through social practices such as religious marriage contracts conducted after civil registration, family mediation based on Islamic values, and inheritance deliberation within domestic spaces. These findings indicate that legal pluralism in China operates in a controlled form, in which religious norms remain socially operative without obtaining formal institutional legitimacy as long as they do not challenge state legal sovereignty. This article contributes to socio-legal scholarship by strengthening the concept of controlled legal pluralism as an analytical model for understanding the survival of Islamic family law in highly centralized non-Muslim states.